Investigation on mechanical properties of expansive lightweight aggregate ultra-high-performance concrete-filled steel tube short columns: Axial compression and interfacial bonding performance - Dengke Wang; Gaozhan Zhang; Hao Chen; Yuqing Hu; Dapeng Qi; Hongzhe Chen (Case Studies in Construction Materials)
To address issues such as debonding and void formation in ultra-high-performance concrete-filled steel tubes (UHPCFST), this study developed an innovative expansive lightweight aggregate ultra-high-performance concrete-filled steel tubes (LUHPCSFT) using pre-wetted lightweight aggregate (LWA) and expansive agent (EA). The research explored the impact of varying amounts of the EA on axial compression and interfacial bonding performance, as well as the effect of steel fiber content on interfacial bonding performance. The results indicate that with an 8 % addition of EA, LUHPCSFT demonstrates the highest axial compressive bearing capacity and interfacial bonding strength (1200KN and 3.3 MPa, respectively), representing increases of 11.6 % and 122 % compared to specimens without the EA. However, the ductility index was reduced, and the deformation resistance was weakened. Incorporating steel fibers can improve interfacial bonding strength, interfacial shear stiffness, and energy dissipation capacity. The combination of expansive lightweight aggregate ultra-high-performance concrete and steel tubes significantly enhances the bearing capacity of CFST structures, resolves the issues of debonding and void formation between the core concrete and the steel tube inner wall, and fosters the development of CFST structures towards large spans, ultra-high-rise buildings, and other advanced applications.